2023
DOI: 10.1101/2023.03.21.533684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactive astrocytes associated with prion disease impair the blood brain barrier

Abstract: Background. Impairment of the blood-brain barrier (BBB) is considered to be a common feature among neurodegenerative diseases, including Alzheimer's, Parkinso'n s and prion diseases. In prion disease, increased BBB permeability was reported 40 years ago, yet the mechanisms behind the loss of BBB integrity have never been explored. Recently, we showed that reactive astrocytes associated with prion diseases are neurotoxic. The current work examines the potential link between astrocyte reactivity and BBB breakdow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Interestingly, this compromise in barrier integrity could be attributed to high levels of IL-6 secreted by reactive astrocytes. Such an increase in IL-6 was observed to reduce the levels of TJ proteins in non-infected mice-isolated endothelial cells within a co-culture model [27], although IL-6 itself is not directly linked to prion diseases progression [66]. Also, TNF-α has been shown to promote a decrease in claudin-5 expression in mice-isolated endothelial cells [67], which may suggest that this cytokine contributes to BBB dysfunction in TSEs when released by activated microglia in response to PrPSc [22].…”
Section: The Blood-brain Barriermentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, this compromise in barrier integrity could be attributed to high levels of IL-6 secreted by reactive astrocytes. Such an increase in IL-6 was observed to reduce the levels of TJ proteins in non-infected mice-isolated endothelial cells within a co-culture model [27], although IL-6 itself is not directly linked to prion diseases progression [66]. Also, TNF-α has been shown to promote a decrease in claudin-5 expression in mice-isolated endothelial cells [67], which may suggest that this cytokine contributes to BBB dysfunction in TSEs when released by activated microglia in response to PrPSc [22].…”
Section: The Blood-brain Barriermentioning
confidence: 88%
“…Recent studies have demonstrated that in prion-infected mice, the integrity of the BBB is compromised prior to the manifestation of clinical symptoms [27]. Furthermore, endothelial cells isolated from these mice exhibit reduced levels of the tight junction proteins occluding and claudin-5, as well as the adherens junction protein VE-cadherin [27]. Interestingly, this compromise in barrier integrity could be attributed to high levels of IL-6 secreted by reactive astrocytes.…”
Section: The Blood-brain Barriermentioning
confidence: 99%
“…Malfunction of AQP4 contributes to the progression of neurodegenerative diseases such as Alzheimer's and Parkinson's disease, and AQP4 autoantibodies cause neuromyelitis optica spectrum disorder (Buccellato, D'Anca, Serpente, Arighi, & Galimberti, 2022;Mader & Brimberg, 2019;Nedergaard & Goldman, 2020;Pittock, Zekeridou, & Weinshenker, 2021). Increased expression and depolarized subcellular distribution of AQP4 has been shown in animal models of neuroinflammation and neurodegeneration such as traumatic brain injury (Ren et al, 2013), local ischemia (Wang et al, 2012), edema (Tourdias et al, 2011), prion disease (Kushwaha et al, 2023) and Alzheimer's disease (Feng et al, 2023;Pedersen, Keil, Han, Wang, & Iliff, 2023;J. Yang et al, 2011).…”
Section: Loss Of Aqp4 Polarity In Covid-19 Patientsmentioning
confidence: 99%